Intraindividual crossover comparison of gadobenate dimeglumine-enhanced and gadoxetate disodium-enhanced MRI for characterizing focal liver lesions - Wenjie Tang; Yuanqiang Xiao; Sichi Kuang; Dailin Rong; Bingjun He; Luigi Grazioli; Shahid M. Hussain; Jin Wang (European Radiology Experimental, 2025)
Abstract Background Gadobenate and gadoxetate are hepatobiliary magnetic resonance imaging (MRI) contrast agents. We intraindividually compared these two agents for the characterization of focal liver lesions (FLLs). Methods A total of 140 adult subjects were randomized to undergo two 3-T MRI exams separated by 7–14 days, one with 0.05 mmol/kg gadobenate and one with 0.025 mmol/kg gadoxetate. For both exams, we acquired the same unenhanced T1-weighted, T2-weighted, and diffusion-weighted sequences, followed by contrast-enhanced T1-weighted sequences during the dynamic and hepatobiliary phases (HBP) (at 20 min for gadoxetate, at 120 min for gadobenate). Three experienced unaffiliated readers independently evaluated each exam in blinded, randomized order for lesion nature (benign/malignant) and specific lesion diagnosis. McNemar test, Wald tests. paired t-tests and κ statistics were used. Results A total of 208 FLLs (108 malignant and 100 benign) were confirmed at final diagnosis. Sensitivity and specificity for malignant/benign differentiation ranged from 91.6% to 99.1% and from 87.5% to 90.5% for gadobenate, and from 86.0% to 91.6% and from 79.7% to 83.6% for gadoxetate. Significantly (p ≤ 0.025) higher values for gadobenate were determined for all diagnostic performance parameters except for sensitivity and negative predictive value for one reader. Significantly (p < 0.001) greater accuracy and confidence for specific lesion diagnosis was achieved with gadobenate for two of three blinded readers. Interreader agreement for malignant/benign differentiation was better with gadobenate (κ = 0.91 versus κ = 0.72). Conclusion Gadobenate was superior to gadoxetate for the differentiation and diagnosis of malignant and benign FLLs for two of three readers. Further confirmatory studies that include a wider representation of different types of FLLs are warranted. Relevance statement Better diagnostic performance and greater confidence in the characterization of FLLs with gadobenate might improve patient management decisions and timings, and potentially lead to better patient outcomes. Key Points Better diagnostic performance for the differentiation of FLLs was achieved with gadobenate for two of three readers. Reader confidence for lesion diagnosis was greater with gadobenate. Superior dynamic phase imaging with gadobenate was crucial for accurate lesion diagnosis. Graphical Abstract